Building A Multicultural Indonesian Nation Through The Mediation Of Self-Identity And Self-Concept - Dwi Mariyono; Maskuri Maskuri (Cita Konsultindo Research Center, 2023)
The combination of cultural frameworks presented by multicultural identity has many advantages in facilitating adaptation. How can someone feel friendly and comfortable with their environment wherever and whenever an individual is. This persistence seems to describe and treat the world as a